Performance analysis and improvement of link adaptation techniques in TDD-HSDPA/SA system - CHEN Shu-ping; DU Jiu-hui; WANG Wen-bo (Tongxin xuebao)
The wireless channel fluctuation resulted from smart antennas in TDD-HSDPA/SA（time division duplex-high speed downlink packet access /smart antennas）system,which caused traditional link adaptation technologies invalid,was theoretically investigated.Two kinds of novel link adaptation schemes were proposed to deal with this issue.A dynamic system level simulator was established to evaluate the performances of the two schemes.Simulation results indicate that both of them have great improvement in system residual BLER and have certain system throughput gain.The first one suits for the hybrid networking case of TDD and FDD（frequency division duplex）mode,while the second one can serve the case of alone TDD networking.